"Bailout" Endovascular Treatment of Acute Aortic Occlusion. (30th April 2018) - Tigkiropoulos, Konstantinos; Stavridis, Kyriakos; Lazaridis, Ioannis; Saratzis, Nikolaos
Abstract : A 37-year-old man who had a recent history of acute myocardial infarction (AMI) 3 months ago presented to the emergency department with acute ischemia of lower limbs. A CT aortography was performed, where left ventricle thrombi and acute thromboembolic occlusion of aortoiliac bifurcation were depicted. He was urgently transferred to the operation theatre, where Fogarty embolectomy was initially unsuccessful. He was managed by primary deployment of balloon expandable (BE) covered stents in the aortic bifurcation followed by thrombectomy of the left ventricle (LV) under extracorporeal circulation by cardiothoracic surgeons 2 days after initial operation. He was discharged in good general condition after 20 days under warfarin and aspirin therapy.